Comparison of Glucose and Satiety Hormone Response to Oral Glucose vs. Two Mixed-Nutrient Meals in Rats - Vannan, Danielle T.; Bomhof, Marc R.; Reimer, Raylene A. (Frontiers in Nutrition, 2018)
The obesity epidemic is driving interest in identifying strategies that enhance appetite control by altering the secretion of hormones that regulate satiety and food intake. An appropriate nutrient stimulus, such as a meal or oral nutrient solution, is needed to elicit the secretion of satiety hormones in order to evaluate the impact of dietary and other interventions. Our objective was to compare the effects of oral glucose versus mixed nutrients on plasma concentrations of glucose and appetite-regulating hormones to determine the most appropriate oral nutrient challenge to trigger robust hormone secretion. A 120min oral glucose tolerance test (OGTT) was compared with two meal tolerance tests (MTT) of differing formulation to evaluate glucose and satiety hormone responses. Following overnight feed deprivation, male Sprague-Dawley rats were given one of three oral gavages with equal carbohydrate content (2g CHO/kg) in the form of: 1) Dextrose, 2) Ensure®, or 3) Mixed Meal. A fourth group was given saline as a control. Blood was collected via tail snip and analyzed for glucose, insulin, GLP-1, GIP, PYY, amylin, leptin and ghrelin. Dextrose resulted in the highest blood glucose at T15 (P=0.014), while the mixed meal was significantly higher than saline from T30-T120 (P<0.05). Insulin was higher at T15 with dextrose compared to saline (P=0.031) and Ensure® (P=0.033). GLP-1 tAUC was significantly higher with dextrose compared to mixed meal (P=0.04) while GIP tAUC was higher with dextrose and mixed meal compared to saline (P<0.05). Changes in tAUC for insulin, amylin, leptin, ghrelin and PYY did not reach significance. Based on these findings, dextrose appears to provide a robust acute glycemic and hormone response and is therefore likely an appropriate oral solution to reproducibly test the impact of various dietary, surgical or pharmacological interventions on glucose and satiety hormone response.